2019
DOI: 10.1038/s41598-019-53019-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-22-3p is involved in gluconeogenic pathway modulated by 3,5-diiodo-L-thyronine (T2)

Abstract: The 3,5-diiodo-L-thyronine (T2) has emerged as an active iodothyronine and its beneficial effects on glucose metabolism including glucose tolerance and insulin resistance is well established. However, little is known about its molecular mechanisms. Given the emerging importance of microRNAs in various metabolic diseases, in this study a possible link between the effects of T2 on glucose metabolism and miRNA expression was investigated by using an in vivo model in which T2 was administered in rats receiving a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…A study in rats showed that upon 3,5-diiodo- l -thyronine (T2) treatment, a drug shown to have beneficial effect on glucose tolerance and insulin-resistance, serum levels of miR-22-3p decreased compared to rats not receiving T2 treatment. This finding is in line with our results in the way that T2 treated rats and non-diabetic controls in our study represent a healthier state, with lower miR-22-3p levels ( 22 ). In addition to miR-22-3p, the miRNAs miR-423-5p and miR-375-3p were also more highly expressed in all diabetes groups compared to control, although differences in these miRNAs were only significant in type 1 diabetes vs controls.…”
Section: Discussionsupporting
confidence: 93%
“…A study in rats showed that upon 3,5-diiodo- l -thyronine (T2) treatment, a drug shown to have beneficial effect on glucose tolerance and insulin-resistance, serum levels of miR-22-3p decreased compared to rats not receiving T2 treatment. This finding is in line with our results in the way that T2 treated rats and non-diabetic controls in our study represent a healthier state, with lower miR-22-3p levels ( 22 ). In addition to miR-22-3p, the miRNAs miR-423-5p and miR-375-3p were also more highly expressed in all diabetes groups compared to control, although differences in these miRNAs were only significant in type 1 diabetes vs controls.…”
Section: Discussionsupporting
confidence: 93%
“…[208][209][210][211][212][213][214][215] T2 administration has also been associated with better glucose tolerance in animal models. It induces inhibition of hepatic gluconeogenesis gene expression [216][217][218] by means of modulation of microRNA, 217 and regulation of the activity of the protein kinase mammalian target of rapamycin complexes 1 (mTORC1) and 2 (mTORC2). 218 Although THs play a role in islet trophic state maintenance, 219 hyperthyroidism impairs glucose-stimulated insulin secretion and accelerates insulin degradation.…”
Section: Adiposity Influencing Thyroid Functionmentioning
confidence: 99%
“…208215 T2 administration has also been associated with better glucose tolerance in animal models. It induces inhibition of hepatic gluconeogenesis gene expression 216218 by means of modulation of microRNA, 217 and regulation of the activity of the protein kinase mammalian target of rapamycin complexes 1 (mTORC1) and 2 (mTORC2). 218…”
Section: Mechanisms By Which Thyroid Function May Interact With Compo...mentioning
confidence: 99%
“…[51] [110,160] miR-26b [111][112][113] [109] miR-135b [115] [114] miR-196b [136] [43,135] miR-22 [117,118,161] [116] miR-532 [120,121,162] [119] miR-20a [123,124] [122]…”
Section: Mir-342mentioning
confidence: 99%